Removal of heavy metals in lake water using bioflocculant produced by Bacillus subtilis - Choong, Chiou Dih; Jamaluddin, Nurul Amirah; Zulkeflee, Zufarzaana (Universiti Putra Malaysia Press, 2019)
Bioflocculant is the extracellular polymeric substances that are produced as by-products of microbial growth with flocculating capabilities. Accordingly, a potential bioflocculant-producing bacterium was isolated from lake water and had been identified as Bacillus subtilis (B. subtilis). The removal of heavy metals from synthetic wastewater and lake water samples that had been treated with bioflocculant produced by the strain was investigated. Synthetic wastewater samples were prepared by spiking the solution with known concentration of Cd, Cr, Cu whereas the lake water samples had been collected from Cempaka Lake, Bangi, Malaysia. Concentration of the metals in the samples before and after treatment by the bioflocculant was measured using ICP-MS. The removal of heavy metals in synthetic wastewater was found to be ineffective without further pH and dosage manipulations. On the other hand, heavy metals found in the lake water samples (Al, Zn, Fe, Cu) were effectively removed at 92.9%, 94.3%, 86.2% and 68.1% respectively; the treatment was optimised at pH 2 (p<0.05), while effects of varying dosages were proven insignificant (p>0.05). Bioflocculant produced by B. subtilis had been proven to be a good alternative to chemically-based solution in remediating heavy metal polluted waters.